Evidence-Based Evaluation of Practice and Innovation in Physical Therapy Using the IDEAL-Physio Framework. Issue 2 (23rd October 2017) - Beard, David; Hamilton, David; Davies, Loretta; Cook, Jonathan; Hirst, Allison; McCulloch, Peter; Paez, Arsenio
Abstract: The IDEAL framework is an established method for initial and ongoing evaluations of innovation and practice for complex health care interventions. First derived for surgical sciences and embedded at a global level for evaluating surgery/surgical devices, the IDEAL framework is based on the principle that innovation and evaluation in clinical practice can, and should, evolve together in an ordered manner: from conception to development and then to validation by appropriate clinical studies and, finally, longer-term follow-up. This framework is highly suited to other complex, nonpharmacological interventions, such as physical therapist interventions. This perspective outlines the application of IDEAL to physical therapy in the new IDEAL-Physio framework. The IDEAL-Physio framework comprises 5 stages. In stage 1, the idea phase, formal data collection should begin. Stage 2a is the phase for iterative improvement and adjustment with thorough data recording. Stage 2b involves the onset of formal evaluation using systematically collected group or cohort data. Stage 3 is the phase for formal comparative assessment of treatment, usually involving randomized studies. Stage 4 involves long-term follow-up. The IDEAL-Physio framework is recommended as a method for guiding and evaluating both innovation and practice in physical therapy, with the overall goal of providing better evidence-based care.